The Effect of Electronic Word of Mouth and Perceived value on Purchase Intention - Nadia Putri Andrian (Enrichment : Journal of Management, 2022)
Indonesia is one of the nations focused on the car market by huge organizations since Indonesia has a high measure of versatility, in 2013 the Ministry of Industry (KEMENPRlN) gave a strategy concerning the minimal expense and harmless to the ecosystem vehicles or regularly known as Low-Cost Green Car. In 2018, 2019 to 2020 Low-Cost Green Car encountered a decline in deals contrasted with the earlier year. This investigation means to clarify the impact of Electronic Word Of Mouth and Perceived Value on Purchase Intention directed by Brand Image with regard to Low-Cost Green Cars in Indonesia. In this study using a quantitative approach and this examination was led in JABODETABEK, utilizing an online poll using google structure appropriated by 150 respondents. Assurance of the example utilizing purposive inspecting. Investigation utilizing way examination or way examination helped by the SmartPLS application. The results of this study indicate that (1) There is an influence between Electronic Word Of Mouth and Purchase Intention on Low-Cost Green Cars in Indonesia. (2) There is an influence between Electronic Word Of Mouth and Brand Image on Low-Cost Green Cars in Indonesia. (3) There is an influence between Purchase Intention and Electronic Word Of Mouth moderated by Brand Image on Low-Cost Green Cars in Indonesia. (4) There is an influence between Perceived Value and Purchase Intention on Low-Cost Green Cars in Indonesia.